Answer :

Formula used:


(2, 2) and (3, 2)


x1 = 2 and x2 = 3


y1 = 2 and y2 = 2


D = √ ((3 – 2)2 + (2 – 2)2)


D = √ ((1)2 + (0)2)


D = √ (1 + 0)


D = √ 1


D = 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the distanceTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I

Show that the folTamilnadu Board Math Term-I